PERAN POLA KONSUMSI TIOSIANAT TERHADAP KEJADIAN GONDOK PADA SISWA SEKOLAH DASAR DI DAERAH ENDEMIK DAN NON-ENDEMIK GONDOK DI KABUPATEN JEMBER - Ningtyias, Faruda Wahyu; Sulistiyani, Sulistiyani; Ratnawati, Leersia Yusi (IKESMA, 2008)
Goitre still become one of especial health problem in Indonesia. Prevalency TGR (Total Goitre Rate) is true tend to downhill, however there is endemic area tendency extend to coastal area and lowland.This research target is know the relation of thiocyanat consumption on the thyroid occurence in area non-endemic (Countryside Wirolegi ) and endemic area (Countryside Kamal) in Regency Jember.This research was inclusive of analytic descriptive. This sample research was consisted of  30 school age children become 2 group, that was thyroid patient group and non thyroid patient group. Goitre identified by palpasi, hereinafter sampel taken  their urine to know the rate of urine iodine and thiocyanat. As supporter data also interviewed by questionnaire to measure food intake and food frequency. Data which have been gathered to be analysed by using Regresi Logistics to see the variable relation with the thyroid occurence.Result of statistical test show there is relation which significant  between rate of Thiocyanat Urine with the thyroid occurence. Thiocyanat has the character of goitrogen personating of competitor and blocking agent in course of thyroid hormone forming. Sufficiency of energy and fat needed in contributing protein function in thyroid hormone forming, insufficiency of protein will bother the thyroid hormone forming process.Concluded that thyroid occurence not because of iodine insufficiency but because height of rate of thiocyanat as well as lowering sufficiency  consume the protein. Hence suggestion which we give is furthermore research to know the source of high and thiocyanat, as well as furthermore research use the more complete indicator, perform the counselling about food processing to eliminating thiocyanat. Keywords : rate of thiocyanat urine, thiocyanat consumption and Goitre